Bioversity International’s contributions to the implementation of article 6 of the International Treaty on Plant Genetic Resources for Food and Agriculture - López Noriega, Isabel; Bedmar Villanueva, Ana (Bioversity International, 2016)
In the last 20 years, Bioversity International has coordinated or has been involved in a number of initiatives, projects and activities that contribute to the implementation of Article 6 of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA). In this note, we summarize how Bioversity International’s work has contributed to each of the measures indicated in Article 6.2 from a) to g) and present examples of projects that are aligned with these measures.